Morfologi dan karakteristik tempat tumbuh tanaman buah merah (Pandanus conoideus Lamk) di Kampung Eroma Distrik Kurima Kabupaten Yahukimo - Philipus Maran; Rima HS Siburian; Hendri (Program Pascasarjana Universitas Papua, 2022)
The red fruit plant (Pandanus conoides Lamk.) is an accession of the pandan plant whose fruit is red and is endemic to Papua. In people who live in the central mountainous area of ​​Papua Province, red fruit is used as daily food. The aim of the research was to study the morphology and characteristics of the red fruit growing area, the traditional development pattern, and aspects of its preservation. The research method used was purposive sampling plot, interviews, local community respondents, field observation techniques and locations were carried out in Eroma Village, Kurima District, Yahukimo Regency, Papua Province. Morphological observations were made on the characters of leaves, stems, roots, spines, and fruit of 2 red fruit cultivars, namely Pandanus conoides long fruit cultivar and Pandanus conoides short fruit cultivar. The characteristics of the growing place that were observed were the availability of soil nutrients and environmental factors, such as weather/climate. Morphological and characteristics data of red fruit grown in gardens and growing wild showed no significant differences. Further analysis to see the interaction of morphology and characteristics of the growing site was carried out using Principal Component Analysis (PCA) and PC8 was found to have good data categories with variance value (0.9341), data variability (3.2%), and cumulative correlation (0.867). The local community still applies the customary system and 13 clans are involved in the management of the red fruit plant. The preservation aspect is carried out in traditional conservation by planting red fruit from seeds and sweeds or taking saplings under the mother tree, taking care of them, and then planting them in their garden area.